RAB26-dependent autophagy protects adherens junctional integrity in acute lung injury. Issue 10 (3rd October 2018) - Dong, Weijie; He, Binfeng; Qian, Hang; Liu, Qian; Wang, Dong; Li, Jin; Wei, Zhenghua; Wang, Zi; Xu, Zhi; Wu, Guangyu; Qian, Guisheng; Wang, Guansong
ABSTRACT: Microvascular barrier dysfunction is the central pathophysiological feature of acute lung injury (ALI). RAB26 is a newly identified small GTPase involved in the regulation of endothelial cell (EC) permeability. However, the mechanism behind this protection has not been clearly elucidated. Here we found that RAB26 promoted the integrity of adherens junctions (AJs) in a macroautophagy/autophagy-dependent manner in ALI. RAB26 is frequently downregulated in mouse lungs after LPS treatment. Mice lacking Rab26 exhibited phosphorylated SRC expression and increased CDH5/VE-cadherin phosphorylation, leading to AJ destruction. rab26 -null mice showed further aggravation of the effects of endotoxin insult on lung vascular permeability and water content. Depletion of RAB26 resulted in upregulation of phosphorylated SRC, enhancement of CDH5 phosphorylation, and aggravation of CDH5 internalization, thereby weakening AJ integrity and endothelial barrier function in human pulmonary microvascular endothelial cells (HPMECs). RAB26 overexpression caused active interaction between SRC and the autophagy marker LC3-II and promoted degradation of phosphorylated SRC. Furthermore, RAB26 was involved in a direct and activation-dependent manner in autophagy induction through interaction with ATG16L1 in its GTP-bound form. These findings demonstrate that RAB26 exerts a protective effect on endothelial cell (EC) permeability, which is in part dependent on autophagic targeting of active SRC, and the resultant CDH5 dephosphorylation maintains AJ stabilization. Thus, RAB26-mediated autophagic targeting of phosphorylated SRC can maintain barrier integrity when flux through the RAB26-SRC pathway is protected. These findings suggest that activation of RAB26-SRC signaling provides a new therapeutic opportunity to prevent vascular leakage in ALI. Abbreviations: AJs: adherens junctions; ALI: acute lung injury; ARDS: acute respiratory distress syndrome; ATG5: autophagy related 5; ATG12: autophagy related 12; ATG 16L1: autophagy related 16 like; 1 BALF: bronchoalveolar lavage fluidCQ: chloroquine; Ctrl: control; EC: endothelial cell; GFP: green fluorescent protein; HA-tagged; RAB26 WT : HA-tagged wild-type; RAB26 HA-tagged; RAB26 QL : HA-tagged; RAB26 Q123L HA-tagged; RAB26 NI : HA-tagged; RAB26 N177I HPMECs: human pulmonary microvascular endothelial cells; H&E: hematoxylin & eosin; IgG: immunoglobulin; GIF: immunofluorescence; IP: immunoprecipitationi;. p.: intraperitoneal; LPS: lipopolysaccharide; PBS: phosphate-buffered salinesi; RNA: small interfering;RNASQSTM1/p62, sequestosome; 1TBS: Tris-buffered saline; VEGF: vascular endothelial growth factor; WB: western blot; WT: wild-type